SURVEY LITERASI DAN INKLUSI KEUANGAN USAHA MIKRO KECIL DAN MENEGAH (UMKM) DI KOTA JAMBI - Simah Anjali; Addiarrahman; Anzu Elvia Zahara (Program Studi Ekonomi Syariah Sekolah Tinggi Agama Islam Negeri Mandailing Natal, 2023)
The purpose of this study was to determine literacy and financial inclusion of Micro, Small and Medium Enterprises (MSMEs) in Jambi City. The method in this study uses a descriptive method with a survey approach. Methods of data collection using observation, surveys, and documentation. The sampling method in this study was to use purposive sampling. Data analysis techniques using analysis according to Miles and Huberman, namely data collection, data reduction, data presentation, drawing conclusions. The results of the study concluded that: (1) there are still many MSMEs that do not have financial literacy; and (2) there are still many MSMEs that do not use financial products. Researchers suggest that: (1) For further research it is advisable to carry out quantitative analysis and use statistical analysis tools; and (2) For further research to increase the number of samples even more so that research can achieve more accurate results. Keywords: Financial Literacy, Financial Inclusion, Micro, Small and Medium Enterprises (MSMEs)